Effect of Nutrient Management Options on Production and Profitability of French Bean (Phaseolus vulgaris L.) in Acid Soil of Arunachal Pradesh - Tasung, Ampee; Kalita, Homeswar; Alone, Rajesh A.; Chanu, Loitongbam Joymati; Angami, Thejangulie; Makdoh, Badapmain; Touthang, Letngam; Das, Shaon Kumar (International Journal of Bio-resource and Stress Management, 2022)
The present study was designed for the standardization of soil nutrient management in increasing the production and profitability of French bean (Phaseolus vulgaris L.) in acid soils of Arunachal Pradesh. A field experiment was carried out in randomized block design with three replications during the rabi season (October–January 2018–2021). The treatment consisted of two French bean cultivars (selection-9 and changlabi local) and 10 nutrient levels [control, vermicompost (Vc), vermicompost+lime (Vc+lime), 50% RDF (Recommended dose of fertilizer), 50% RDF+lime, 50% RDF+Vc, 75% RDF, 75% RDF+lime, 75% RDF+Vc, 100% RDF]. The doses of vermicompost, lime and RDF were 2.5 t ha-1, 400 kg ha-1 and 50-50-50 NPK kg ha-1. The results observed among the soil nutrient management, treatment 75% RDF+Vc recorded minimum values of 50% days to flowering (41.7 DOS) and maximum values of pod length (14.8 cm), the number of pod plant-1 (7.17) and yield (4,654 kg ha-1). This treatment also recorded maximum gross and production efficiency. The B:C ratio of 75% RDF+Vc and 75% RDF+lime treatment was recorded above 1.50, irrespective of the cultivar. Between the cultivar, selection-9 obtained higher values of yield attributes, yield, gross return, production efficiency and B:C ratio than changlabi local. Thus, based on French bean crop yield and yield attributes, 75% RDF along with Vc @ 2.5 t ha-1 was superior, irrespective of cultivar and between the cultivars, selection-9 was superior.